HAEMODYNAMIC AND HUMORAL FACTORS OF NORMOSTRESSED AND HYPERSTRESSED LEFT VENTRICULAR HYPERTROPHY AT MODERATE ARTERIAL HYPERTENSION - Manik, Ibrahim Moosa (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
In the basis of haemodynamics at arterial hypertension with normostressed left ventricular hypertrophy, lie the changes of direction to preserving contractility of myocardium. The compensatory mechanisms include: The higher the activity of metalloproteinase-1 and it’s inhibitor, the lower the activity of transforming growth factor-β1, endhothelin-1, aldehyde phenylhydrazone, Superoxiddismutase, FAS-ligand and higher the general anti-oxidant activity. In the basis of haemodynamics at arterial hypertension with hyperstressed left ventricular hypertrophy, lie the decrease of myocardium contractility and increase of common peripheral vascular resistance. Humoral regulation is characterized by dominating the process of connective tissue degradation over cardiomyocyte apoptosis.